Aseismic slip and seismogenic coupling along the central San Andreas Fault. Issue 2 (22nd January 2015) - Jolivet, R.; Simons, M.; Agram, P. S.; Duputel, Z.; Shen, Z.‐K.
Abstract: We use high‐resolution Synthetic Aperture Radar‐ and GPS‐derived observations of surface displacements to derive the first probabilistic estimates of fault coupling along the creeping section of the San Andreas Fault, in between the terminations of the 1857 and 1906 magnitude 7.9 earthquakes. Using a fully Bayesian approach enables unequaled resolution and allows us to infer a high probability of significant fault locking along the creeping section. The inferred discreet locked asperities are consistent with evidence for magnitude 6+ earthquakes over the past century in this area and may be associated with the initiation phase of the 1857 earthquake. As creeping segments may be related to the initiation and termination of seismic ruptures, such distribution of locked and creeping asperities highlights the central role of the creeping section on the occurrence of major earthquakes along the San Andreas Fault. Key Points: Significant strain buildup along the SAF creeping segment Discreet asperities in the transition zones on the edges of the creeping segment Creeping segment may have a role on the initiation of past and future earthquakes